Narratives of partners of people diagnosed with bipolar disorder - Pienaar, Mia (My University, 2016)
Bipolar disorder is a chronic, turbulent mental disorder that is associated with feelings of distress and ‘caregiver burden’ for those who are close to people diagnosed with it. Although there is a relatively large body of literature on ‘caregivers’ of people with chronic mental illness, it is argued that this body of research has been reductionist and one-dimensional. Furthermore, the extant research has, in general, treated any person close to someone with bipolar disorder as a ‘caregiver’, without giving attention to the unique relational dynamics between two people. This is especially true for romantic partners of people with mental illness. This study used a social constructionist approach and a narrative methodology to analyse individual interviews with five people who are or had been in an intimate relationship with someone with bipolar disorder. This study used Bamberg’s (1997) positioning analysis to explore the ways in which the participants constructed important characters, their audience and themselves in their narratives of living with someone with bipolar disorder. It was found that there are many more possibilities for dynamics between a person and his or her partner with bipolar disorder than a simple caregiver-care receiver dynamic. It was also found that for the participants the term ‘caregiver’ is not an appropriate description of their role and position. This research is important as an example of embracing the complexity of family members’ experiences of mental illness, and to open the possibility of narrative intervention for partners of people with bipolar disorder
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts in Psychology. 2016
Keywords: Manic-depressive illness; Caregivers--Psychology